FORMATION AND DEVELOPMENT OF CIVIL SOCIETY IN UZBEKISTAN - Kholikulov P. (Sciental Journals Publishing, 2025)
The article reveals the evolution of the formation of civil society, its legal foundations, its active participation in the life of society and the state. The most fundamental and main advantages of civil society are these divine blessings - freedom and independence, as well as their implementation without any obstacles. This has been achieved in Uzbekistan over the years of independence. This is evident in the growth of political consciousness and legal culture of citizens.
Keywords: Rule of law, state power, democracy, citizens, civil society, civil society institutions, decentralization, state, self-government, mass media, non-governmental non-profit organizations, mass movements. exact.